2016
DOI: 10.1002/acr.22900
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Post‐Chikungunya Infection Chronic Inflammatory Arthritis: A Systematic Review and Meta‐Analysis

Abstract: According to our results in the most conservative scenario, approximately 25% of CHIK cases would develop CHIK-CIR (34% if we just consider the most representative studies), and 14% would develop chronic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
134
1
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 46 publications
15
134
1
15
Order By: Relevance
“…At 12 months, case-patients were significantly (p<0.01) more likely than controls to report difficulty performing daily activities. Our unadjusted persistent arthralgia estimates at 6 (44%) and 12 (33%) months (Table 2) fall within the pooled estimate from a metaanalysis (40%, 95% CI 31%–49%) ( 4 ). …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…At 12 months, case-patients were significantly (p<0.01) more likely than controls to report difficulty performing daily activities. Our unadjusted persistent arthralgia estimates at 6 (44%) and 12 (33%) months (Table 2) fall within the pooled estimate from a metaanalysis (40%, 95% CI 31%–49%) ( 4 ). …”
Section: Discussionsupporting
confidence: 77%
“…Although acute symptoms of CHIKV infection are well-documented ( 12 ), information on the prevalence of long-term sequelae remains limited to observational studies, many of which lack comparator groups ( 4 ). From our year-long study of 165 case-patients and 167 controls, we found an almost 3-fold increased risk for persistent arthralgia in CHIKV case-patients at 6 and 12 months after illness onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following acute infection, typically lasting for 1-2 weeks, approximately 35% of patients develop a second phase of illness; disabling, potentially chronic arthritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…over 15,000 cases in Colombia during January-June, 2016) [2]. In this context, not only rheumatological compromise is important [3]. Recently, some authors have suggested that cardiovascular disorders such as arrhythmias, myocarditis, pericarditis, myocardial infarction have occurred in previously healthy cases [4].…”
Section: Dear Editormentioning
confidence: 99%